O lugar do campo na forma??o do t?cnico em agropecu?ria no IF Baiano ? Campus Catu - Abreu, Luciane Ferreira de (2014)
In this research, I take as object of study the discussed the education of the Agricultural Technician in the Instituto Federal de Educa??o, Ci?ncia e TecnologiaBaiano, (IF Baiano) - Campus Catu, where I work as an educator . The dynamic implementation of the Technical Course on the Integrated Agricultural High School, marked by several problems of political and educational, has provoked the following questions: How to setup the proposed formation of Agricultural Technician in that course? What is the profile of the formation of the proposed Agricultural Technician? What is the perception of teachers and students of the course on the design and effectiveness of the proposed integrated curriculum? So we have to analyze the proposed formation of Agricultural Technician at IF Baiano - Campus Catu in the period 2006-2012, in the light of the discussions of Vocational Education and Field of Education. Perceive through the critical studies in these areas both towards a common horizon: polytechnic formation of subjects as coping strategy project capitalist society, so we understand to be necessary to expand the discussions on vocational education and aggregate problematizations that have been generated by reality job field. The study is characterized as a research and descriptive research method chosen as the case study in order to know the process of formation of Agricultural Technician as a complex social phenomenon, analyzing it from the perspectives of socio - historical circumstances that produced the current frame of Vocational Education and Rural Education in the country. And qualitative procedures for obtaining the data, first use bibliographic and documentary research, guided by theoretical studies and official documents IF Baiano. Following, we conducted a survey on interviews with teachers, students, director of education and local representative of the rural workers union. As an initial observation, we noticed that the training proposal Agricultural Technician at Campus Catu constituted by practices and guidelines related to heterogeneous conceptions that approach the ideas of agribusiness and training to the labor market. But on the other hand, we observed that this discourse is not homogeneous or permanent trainers by subjects, some of them think of different alternatives as a counterpoint from the perspective of human, or are proving receptive to discussion of the topic. It is in this space that we look on the necessary association between the training proposal and contradictory reality of the field under the foundations of the field of Rural Professional Education.